2019
DOI: 10.3747/co.26.4595
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Nivolumab and Cabozantinib in Metastatic Renal Cell Carcinoma: Results from the International Metastatic Renal Cell Carcinoma Database Consortium

Abstract: Objectives In the present study, we explored the real-world efficacy of the immuno-oncology checkpoint inhibitor nivolumab and the tyrosine kinase inhibitor cabozantinib in the second-line setting.Methods Using the International Metastatic Renal Cell Carcinoma Database Consortium (imdc) dataset, a retrospective analysis of patients with metastatic renal cell carcinoma (mrcc) treated with nivolumab or cabozantinib in the second line after prior therapy targeted to the vascular endothelial growth factor receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
1
24
1
1
Order By: Relevance
“…This study is for sure the largest evaluation of cabozantinib in nccRCC population and confirmed previous real-world data evaluating the use of cabozantinib in smaller population of nccRCC (15)(16)(17)(18)(19).…”
supporting
confidence: 87%
“…This study is for sure the largest evaluation of cabozantinib in nccRCC population and confirmed previous real-world data evaluating the use of cabozantinib in smaller population of nccRCC (15)(16)(17)(18)(19).…”
supporting
confidence: 87%
“…In addition to insufficient clinical trial data, there is little real-world evidence in Japanese patients. While there are several reports from other countries [13][14][15][16] and some analyses of patient groups excluded from CheckMate 025 [17], no similar multicenter or large-scale analyses have been reported in Japan. This clinical study was planned to analyze the treatment patterns of nivolumab for mRCC patients in clinical practice, and the efficacy and safety of nivolumab for these patients, by retrospective analyses of information from medical records.…”
Section: Introductionmentioning
confidence: 97%
“…Promising treatment schemes for metastasized renal cell carcinoma have been reported [9,10], but they mostly concern ccRCC, and there is still no specific therapy for CDC. However, there are treatment suggestions for metastatic CDC, i.e., first-line therapy with a combination of chemotherapy (gemcitabine) plus cisplatin/carboplatin, and second-line therapy as a targeted therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%